Digital Innovation in the Era of Society 5.0 Encourages Indonesia's Economic Recovery in Post-Pandemic - Suyanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to examine the role of digital innovation in driving Indonesia's economic recovery in the post-pandemic era through the Society 5.0 approach. The global Covid-19 pandemic has had a significant impact on the Indonesian economic sector, which requires innovative steps to restore the country's economy. Society 5.0, which is a concept promoted by the Japanese government, combines digital technology with social and human needs to achieve a sustainable and inclusive society. This study uses a qualitative approach by collecting data from various sources such as literature, research reports, and case studies related to digital innovation that has been implemented in Indonesia. The research results show that digital innovation has a crucial role in driving Indonesia's economic recovery in the post-pandemic era. Some of the digital innovations identified include e-commerce, fintech, big data, artificial intelligence (AI), and the Internet of Things (IoT). The application of digital innovation has enabled the economic sector to adapt to new situations, accelerated digital transformation, and expanded access to global markets. This research provides in-depth insight into the role of digital innovation in driving Indonesia's economic recovery in the post-pandemic era. These findings can serve as a basis for policy makers, business people and the general public in developing innovative strategies that can take advantage of digital potential to accelerate the country's economic recovery